2010
DOI: 10.1149/1.3294790
|View full text |Cite
|
Sign up to set email alerts
|

Aging Mechanisms of LiFePO[sub 4] Batteries Deduced by Electrochemical and Structural Analyses

Abstract: The performance loss of lithium-ion batteries with lithium iron phosphate positive chemistry was analyzed using electrochemical characterization techniques such as galvanostatic charge–discharge at different rates, ac impedance, and hybrid pulse power characterization measurements. Differentiation analysis of the discharge profiles as well as in situ reference electrode measurement revealed loss of lithium as well as degradation of the carbon negative; the cell capacity, however, was limited by the amount of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
203
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(225 citation statements)
references
References 51 publications
14
203
1
Order By: Relevance
“…The differentiation analysis of the discharge profiles as well as in situ reference electrode measurements revealed loss of lithium as well as degradation of the carbon anode [33], whereas Dubarry et al [35] reported that the cells suffer severe degradation at 60°C and that the electrochemical milling of grains could explain the observed degradation as it might cause loss of active material in the positive electrode by isolating grains from the percolation pathway, which may also induce a loss of Li inventory, due to SEI formation on the fresh surface created, especially at elevated temperatures. Safari et al [37] identified the depletion of cyclable lithium and the partial loss of graphite active-material particles as the two contributors to the capacity decline of the cells aged by cycling and storage at 25 and 45°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differentiation analysis of the discharge profiles as well as in situ reference electrode measurements revealed loss of lithium as well as degradation of the carbon anode [33], whereas Dubarry et al [35] reported that the cells suffer severe degradation at 60°C and that the electrochemical milling of grains could explain the observed degradation as it might cause loss of active material in the positive electrode by isolating grains from the percolation pathway, which may also induce a loss of Li inventory, due to SEI formation on the fresh surface created, especially at elevated temperatures. Safari et al [37] identified the depletion of cyclable lithium and the partial loss of graphite active-material particles as the two contributors to the capacity decline of the cells aged by cycling and storage at 25 and 45°C.…”
Section: Introductionmentioning
confidence: 99%
“…It is safe, because of a high thermal stability, and has a low toxicity and a low cost compared to cathodes such as LiCoO 2 . Several aging studies concerned with life performance of LFP-based cells are found in the literature [26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Again, lithium inventory loss is found to be the main cause of the capacity degradation of the LFP-based cell. Liu et al [64,65] investigated the discharge profiles using a differential analysis, and they confirmed that the loss of reversible Li is responsible for most of capacity fade. They also used external lithium source to replenish the cycled cathode which has lost 30 % of its capacity after 2,730 cycles.…”
Section: Sphericalmentioning
confidence: 95%
“…Commonly used reference electrodes are inserted into the cell prior to the sealing of the outer casing material; [15][16][17][18] however, this approach is not amenable to mass production and may alter the performance of the cell relative to one without an inserted reference electrode. Liu et al 6 utilized a reference electrode by removing the end cap of a cylindrical cell and immersing both the cell and reference electrode in an electrolyte-filled vessel, with the reference electrode located outside of the cell. 19 These researchers conducted a cycle-aging regime on a cell in this configuration and reported voltage of the negative electrode (vs.…”
mentioning
confidence: 99%